Lingkungan Eksternal dan Internal Pengaruhnya terhadap Kemitraan dan Kinerja Usaha Kecil Makanan Mie di Provinsi Sulawesi Selatan - Muis Dilla; Anwar Anwar; Tenri S. P. Dipoatmodjo (Seminar Nasional LP2M UNM, 2019)
The research methodologies used were descriptive verificative and explanatory survey. The technique used was cross section. This means the research was conducted in a certain period of time to 72 respondents through interview and questionnaire. The sampling technique was simple random sampling. The data were analyzed using descriptive analysis and path analysis. Based on data analysis, this research shows that : external environment (economy, politics, law, technology and sosiocultural), internal environment (resources, organization culture, and structure), business partnership (capital, nurturing, management and business correlation) and small business work performance in the view of Balanced Scorecard (perspective of finance, customer, internal business process, learning ang growth) in small scale industry in South Sulawesi have significant influence among others; 1) external and internal environment give significant influence to partnership and work performance; 2) external and internal environment give significant influence to partnership of small scale noodel industry in South Sulawesi; 3) business partnership gives significant influence to work performance of small scale noodle industry in South Sulawesi; 4) business partnership, internal and external environment, partially and simultaneously, give significant influence to work performance of small scale noodle industry in South Sulawesi; 5) internal environment gives more influence to small scale work performance then external environment and business partnership.